KELEMAHAN PENGATURAN PENGUPAHAN BAGI DOKTER DI INDONESIA - Nur, Muhammad (UI Scholars Hub, 2021)
The results of the Junior Indonesian Doctors Network (JDN) survey on August 1-30 2018 stated that 26.24 percent of doctors in Indonesias main workplaces were still paid under three million rupiah per month. Then, there are 8.89 percent of doctors who are even paid under one and a half million rupiah per month. Due to the low salaries earned, many doctors end up having to take additional work hours in several practice locations to increase their income. In fact, other studies say that working continuously for doctors increases the risk of malpractice and endangers patients. Low wages also make doctors apathetic about their work and find it difficult to empathize with patients so they do not provide the best service for them. In addition, low wages also triggered collaborative practice between pharmaceutical companies and doctors to increase their respective income. This study found that the low salary of doctors was caused by the weaknesses of the legislation, the weaknesses of the regulations of the doctor profession in Indonesia, and the weaknesses of work agreements.